Glass Bead Making Technology in Ancient Sri Lanka - Buddikasiri, P.R.A.; Madhumali, A.K.R. (Journal of Archaeology, Tourism & Anthropology, 2020)
Bead making and trading of beads are some of the oldest industries in the world. Beads are small, colourful, symmetrical, and often quite beautiful. They are frequently standardized, inexpensive units that can be arranged in almost endless configurations. They can be seen not only in familiar forms of necklaces and bracelets but also on anklets, headbands, and headdresses. Beads are small, but important finds from Archaeological investigations. Especially, the discovery of beads creates enormous interest among the excavator, researchers and laymen. It provides excellent information to the understanding of various aspects of the human past. While a couple of studies surmise of bead production no study has been confined to study the bead making industry in Ancient Sri Lanka. Therefore, the purpose of this study is to examine if there was a glass bead making technology in Ancient Sri Lanka. It is hoped to study the glass bead making technology of the past based on the archaeological data uncovered through archaeological research conducted in Sri Lanka. This study focuses on the traditional analysis method. Mantai, Kantarodai, Tissamaharama,Kirinda, Abhayagiriya, Ridiyagama Giribawa and Ridiyagama is one of the leading areas in the study of glass beads design technology in Sri Lanka
Keywords: Beads making, Drawn, Glass Beads, Technology, Wound